ANALYSIS OF CHANGES IN SYSTOLIC AND DIASTOLIC HEART DYSFUNCTION AS A RESULT OF LIVER CIRRHOSIS - Abdiraxmon Toxir o‘g‘li, Muhammadqulov; Faridun Sharifovich, Zohidov; Tolibova , Shodiya Shomamatovna (Educational Research in Universal Sciences, 2024)
In clinical and instrumental examination of 98 patients with cirrhosis of the liver by means of Echo-CG in M-regimen, in 85,0% of cases damage to the heart was revealed. The basis of damage to the heart was presented by hypertrophy of the left ventricle and myocardial dystrophy that resulted in disturbance of contractive function, diastolic and systolic dysfunction. Damage to the heart in its turn contributed to the development of chronic cardiac insufficiency and increase of portal hypotension degree.